Pengaruh Brand Ambassador, Brand Image, Harga, Kualitas Produk, dan Promosi Terhadap Keputusan Pembelian Skincare Glad2glow Pada Mahasiswi Feb Its Mandala Jember Angkatan 2022 - Himatul Aliyah; Nurshadrina Kartika Sari; Karim Budiono (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the influence of Brand Ambassador, Brand Image, Price, Product Quality, and Promotion on the Purchase Decision of Glad2Glow skincare among female students of the Faculty of Economics and Business, ITS Mandala Jember, Class of 2022. This study used a quantitative approach with data collection techniques through questionnaires. The population in this study were female students of the Faculty of Economics and Business, ITS Mandala Jember, Class of 2022 who had purchased and used Glad2Glow skincare products. The sampling technique used purposive sampling with a total of 100 respondents. The data analysis method used was multiple linear regression with SPSS, as well as through validity and reliability tests, classical assumption tests, t-tests, and F-tests. The results showed that partially, Brand Ambassador, Price, and Promotion had a significant influence on the Purchase Decision of Glad2Glow skincare. Meanwhile, Brand Image and Product Quality did not have a significant influence on the Purchase Decision. Simultaneously, Brand Ambassador, Brand Image, Price, Product Quality, and Promotion had a significant influence on the Purchase Decision of Glad2Glow skincare.